Strategi Dakwah Multikultural Dalam Menangkal Islamofobia - Mahmuddin, Mustawi (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
Islamophobia has experienced a significant increase in recent times, not only in Western countries but also in Muslim-majority nations. This phenomenon, which constitutes a form of discrimination and irrational fear toward Islam, continues to proliferate rapidly in the digital and globalization era, thereby impacting intercommunity relations. This study examines multicultural dawah strategies as a primary instrument to counteract Islamophobia through inclusive and dialogic approaches. Employing qualitative methods based on content analysis and case studies from diverse contexts, the research identifies strategies such as inclusive education, interfaith dialogue, and the utilization of digital media. The findings indicate that multicultural dawah can reduce stereotypes, foster empathy, and promote social tolerance. The implications of this study include recommendations for dawah practitioners, educational institutions, and policymakers to implement these strategies on a broader scale. This research contributes to efforts in building a harmonious society amidst cultural diversity. Keywords: Multicultural Da'wah Strategies, Countering Islamophobia